Teaching English Vocabulary to Young Learners via Augmented Reality Learning Media - Agata, Dias; Yuniarti, Heny; Adison, Ahmelia Ayu Pratiwi (Widya Mandala Surabaya Catholic University, 2021)
This research aims to investigate the effect of teaching English vocabulary to young learners via Augmented Reality learning media. The subject of this research was 12 students of grade 1 elementary school. Due to strict health protocols during COVID-19 outbreak, the testing phase was done in students' respective homes accompanied by their parents using cell phones. Vocabulary illustrated in 30 three-dimensional objects and their written form were generated through cell phone’s scanning. A quiz consisted of 54 multiple choice questions was provided after the interactive learning experience. Both the vocabulary and quiz were refer to Thematic English Exploration for Grade 1 book. The results showed that learning vocabulary using AR application was able to increase the mean evaluation score by 0.77%. This application is effective in helping students improve their English language skills as approved by 76% of parents. The AR application was also approved by 59% of parents that it was easy to use. The AR application is proven to be convenience for students to learn English vocabulary interactively and feasible to be used as learning media.